The influence of global digital trends on the shadow economy: theoretical and legal aspect - Budnyk , Liudmyla; Danuliuk, Iryna; Tyhach, Hrygorii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The problem of digitization in the shadow economy remains relevant in the modern world. Digital technologies can be both tools for combating the shadow economy and means it can use for its functioning and development. The purpose of the article is to study the theoretical and legal aspects of the impact of global digitization trends on the shadow economy. Based on the study of scientific sources, the concept of the digital shadow economy is defined as a hidden, informal, illegal, criminal activity that is carried out using digital technologies and is aimed at obtaining profit or other material or non-material benefit. The description of the tools that contribute to the fight against the shadow economy in the conditions of the use of digital technologies is given. The use of digital tools makes it possible to optimize the control systems of economic activity, identifying and monitoring shadow operations for more effective supervision by the authorities. New challenges and threats to cyber security, and directions for improvement of legal mechanisms for protection against cybercrimes and cyberattacks substantiated. In the conditions of digitalization, new challenges arise for legal regulation. Legislation needs to be adapted effectively control the shadow economy in the online environment.